India : Strategic Assessment for Innovative and Transformative Change in Delivering Urban Environment Services in Amritsar and Ludhiana - World Bank Group (Washington, DC, 2015)
The Government of Punjab, through Government of India’s (GoI) Department of Economic Affairs (DEA) had requested the World Bank to provide non-lending technical assistance (NLTA) to provide high quality basic urban civic amenities to the residents of cities of Ludhiana and Amritsar in the areas of: water supply, sewerage, storm water drainage, solid waste management, and modern urban transport system. The study is expected to recommend measures and technologies to overcome the existing problems and transform the cities in to modern cities with substantially developed urban civic amenities. Capacity building, institution, and legal reforms will also be the component of the project report. After initial discussions with sector officials, a Bank team visited both Amritsar and Ludhiana cities to identify priority service level innovations and institutional challenges that have to be addressed under this NLTA for achieving desired transformative change. Currently, water supply is drawn from hundreds of unprotected bore wells across length and breadth of the city - which supply polluted water through an unplanned haphazard network. Utility, fully owned by the municipal corporation, will have operational autonomy to manage water and waste water services, whilst still be accountable to the corporation. Financial position will become clear, it can focus on becoming financially self-sustaining. The utility will make long term plans for water supply and sewage; and with government support may also be able to mobilize resources through this is unlikely in the short term in Amritsar.